Biodegradation of tannery effluent by using tannery effluent isolate - Ingole, Sangita P; Kakde, Aruna U; Maggirwar, R C (International Multidisciplinary Research Journal, 2012)
Water is one of the most important constituent of life support system. Metals, pesticide, and large number of complex organic chemicals which are prepared through man made activities, pose serious threat to the life of mankind. Bioremediation is a process that uses naturally occurring or genetically engineered microorganism such as yeast, fungi and back to transform harmful substances. Tannery is one of the emerging sectors in industrialisation. The tannery effluent has high pollution potential. It creates serious threat to human and entire ecosystem. Biological detoxification turns to be similar, cheaper and significant. In present investigation Pseudomonas sp. was isolated from tannery effluent and its degradation on efficiency was analysed by comparing changes in the physicochemical and organic analysis of the tannery effluent before and after bacterial treatment. The results revealed that the toxic effects were mostly reduced after treatment, making the treated effluent suitable to be discharged into the environment.